PERAN GURU DALAM MENDORONG AKTIVITAS GOTONG ROYONG MELALUI LINGKUNGAN BELAJAR KOLABORATIF - Aulia Intan Rahayu, Amelia Putri Amanda, Hanifa Nur Azizah, Lusi Diah fatmawati, Chriswanda Hafidz N (JURNAL ILMU PENDIDIKAN, 2026)
This study aims to describe the role of teachers in fostering mutual cooperation values through the application of a collaborative learning environment at SD Negeri Gadingkulon 2. The main problem underlying this study is the weak practice of mutual cooperation among elementary school students, which is influenced by increasing individualism and a lack of opportunities to work together in learning activities. This study uses a qualitative approach with a case study method to gain an in-depth understanding of teacher strategies, student interactions, and factors that influence the effectiveness of collaborative learning. Data were collected through observation, interviews, and documentation, then analyzed through reduction, presentation, and conclusion drawing stages. The results showed that teachers played an important role in designing group tasks, facilitating student communication, and setting an example of mutual assistance. The collaborative learning environment was found to encourage students to be more active, responsible, and able to work together in groups. However, its implementation faced obstacles in the form of differences in student abilities, the dominance of certain groups, and limited learning time. This study concluded that the collaborative learning environment is an effective approach to fostering a spirit of mutual cooperation when supported by adaptive classroom management strategies and a conducive school culture.